2020
DOI: 10.1111/nicc.12564
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of family engagement interventions in neonatal, paediatric, and adult ICUs

Abstract: Aims and objectives: The purpose of this systematic review was to evaluate interventions that have been used to engage families in direct care activities (active family engagement) in adult, paediatric, and neonatal intensive care unit (ICU) settings.Background: Family engagement is universally advocated across ICU populations and practice settings; however, appraisal of the active family engagement intervention literature remains limited. Search strategy: Ovid Medline, PsycArticles & PsycInfo, Scopus, and CIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
(333 reference statements)
0
13
0
Order By: Relevance
“…Interventions that enable caregivers to actively participate in patient care in the ICU are urgently needed to mitigate the negative symptom sequelae experienced by family caregivers during and after the ICU and to better prepare them for new caregiving demands after hospital discharge (Davidson et al, 2017; McAndrew et al, 2020a). Because ICU family engagement science is still emerging, evidence-based, standardized tools to evaluate family caregiver characteristics and preferences have yet to be established, leaving clinicians with few tools and resources to support family involvement in care.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that enable caregivers to actively participate in patient care in the ICU are urgently needed to mitigate the negative symptom sequelae experienced by family caregivers during and after the ICU and to better prepare them for new caregiving demands after hospital discharge (Davidson et al, 2017; McAndrew et al, 2020a). Because ICU family engagement science is still emerging, evidence-based, standardized tools to evaluate family caregiver characteristics and preferences have yet to be established, leaving clinicians with few tools and resources to support family involvement in care.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was extended to families in subsequent years ( Davidson & Strathdee, 2019 ). Parallel changes can be observed since 1955 in paediatric care, when attention focused on the importance of parents' presence in enhancing the sensorimotor and emotional development of new-born children (Gomez-Cantarino et al, 2020; McAndrew et al, 2020 ). Family-centred care considers patients’ complexity, including the psychosocial, economic and genetic context of their families, with consequences for their medical history and present condition ( Davidson et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the FCC, clinician and family engagement is informed by mutual respect and shared decision-making, generating psychosocial support and allowing for the allocation of hospital resources to attain the goal of family well-being and involvement [ 14 ]. Indeed, a recent systematic review indicated that the FCC approach contributes to improvements in mothers’ mental health [ 42 ]. As such, the FCC model is the basis of the approach taken by the NICU where the current study was conducted.…”
Section: Introductionmentioning
confidence: 99%